Determining indoor thermal comfort condition of Kutai House through bioclimatic analysis / Mohamad Zaki Yusof, Husna Afifi and Suzana Said - Yusof, Mohamad Zaki; Afifi, Husna; Said, Suzana (Universiti Teknologi MARA, Perak, 2020)
Conserving the traditional Malay Kutai houses as our building heritage is important before they perish due to neglection. For maintenance purposes, the palm leave roofs are replaced with more durable materials such as zinc or onduline roof sheets. Replacing the building materials without understanding their properties could cause harmful effect on the indoor thermal comfort. Previously, there is minimal quantitative research done to prove that the traditional Malay house is thermally comfortable. Thus, this research intends to measure the thermal comfort parameters of Kutai house and analyse the result using a bioclimatic chart. The results revealed that the average thermal comfort conditions of the Kutai houses are within the boundaries of comfort zone as recommended for natural ventilated buildings despite using zinc roof.